Pembuatan Purwarupa Ensiklopedia Tarian Adat Minangkabau - Wahyuni, Fitri; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2019)
AbstractIn this paper we discuss Minangkabau traditional dances in the form of an encyclopedia prototype. The objectives of writing this paper are: (a) to describe the community's needs for information about Minangkabau traditional dances; (b) describes the process of making an encyclopedia of traditional Minangkabau dance prototypes; and (c) describe the constraints and efforts in making an encyclopedia prototype of Minangkabau traditional dance. This study uses a descriptive method with data collection techniques through direct observation and direct interviews with seven different professions, such as the community, students, students, tourists and owners of the Syofyani dance studio. Based on the analysis of the data it can be concluded as follows: First, the need for information about Minangkabau traditional dances is very minimal from the community, this can be seen from people who are not very interested in information about Minangkabau traditional dances because Minangkabau traditional dances are rarely performed and there are no information media which specifically discusses Minangkabau traditional dances. So that the Minangkabau traditional dance is shifted by outside dances such as dance and k-pop. Second, the making of an encyclopedia prototype of Minangkabau traditional dance through several stages, namely: (a) information needed about traditional Minangkabau dances; (b) data collection is done by interviewing techniques; (c) prototype product design encyclopedia of Minangkabau traditional dance using the Photoshop CS6 application; and (d) the resulting form is an encyclopedia prototype which contains information about the types of dance, dance philosophy, property used, music, clothing used in the dance, along with supporting images. Third, constraints and efforts in producing encyclopedias prototype products, namely: (a) resource persons who know about information about Minangkabau traditional dances are difficult to find and efforts to overcome them are done by making an appointment beforehand to the speakers; (b) data collection such as books on Minangkabau traditional dances is difficult to obtain and efforts to determine them are carried out by obtaining data from journals that discuss traditional dances.Keywords: Prototype, Encyclopedia, Minangkabau Indigenous Dance